Cholescintigraphy may have a role in selecting patients with biliary dyskinesia for cholecystectomy: a systematic review. Issue 9 (1st June 2020) - Alhayo, Sam; Eslick, Guy D.; Cox, Michael R.
Abstract: Background: Patients with typical biliary pain, no gallstones on ultrasound and low gallbladder ejection fraction (GBEF) on cholescintigraphy (gallbladder dyskinesia) may be considered for a laparoscopic cholecystectomy. However, some studies have suggested that symptoms alone are an adequate indication for laparoscopic cholecystectomy. The aim was to determine the role of cholescintigraphy in predicting outcomes of cholecystectomy in patients with typical and atypical biliary symptoms and normal biliary ultrasound. Methods: Meta‐analysis using Preferred Items for Systematic reviews and Meta‐Analysis (PRISMA) guidelines of published literature using several electronic databases. Results: Twenty‐four articles were selected with a total of 1710 patients. The majority ( n = 1633, 94.4%) of patients had typical biliary symptoms. A total of 1047 patients with typical symptoms and a reduced GBEF had a cholecystectomy with 852 (81.4%) having complete resolution of symptoms. A total of 148 with typical symptoms and normal GBEF had a cholecystectomy with 103 (69.5%) having complete resolution, which was significantly less than those with a reduced GBEF (odds ratio 1.65, confidence interval 1.08–2.05, P = 0.01). Forty‐five patients with atypical symptoms and a reduced GBEF had a cholecystectomy with 31 (68.9%) having complete resolution of symptoms, which is significantly lower than those with typical symptoms (odds ratio 1.97, confidence interval 0.95–3.90, P = 0.05). Conclusion: Cholescintigraphy improved the predication of outcome of cholecystectomy in biliary dyskinesia by 10%. However, the presence of typical symptoms does predict an effective response in 70% of patients. Atypical symptoms predict a poorer response.